Activists' stories facilitating migrant rescue operations in the Mediterranean sea - Garziz, Sinda (Université d'Ottawa | University of Ottawa, 2024)
This research paper explores the intersection of migrant justice activism, border imperialism, and creative research methodologies, focusing on the Mediterranean border crisis. Through an in-depth and creative analysis of activists’ narratives from the Alarm Phone, this research highlights how irregular migration is framed as a form of resistance against colonial and capitalist structures that perpetuate global inequalities. Drawing on Harsha Walia’s concept of Border Imperialism, the study critiques Europe’s militarized border policies, exposing the complicity of European states in migrant deaths. Using personal narratives and creative documentation, this research amplifies the voices of activists who challenge dehumanizing discourses about migration. Grounded in over a decade of migrant justice activism, this work incorporates artistic elements, presenting its findings through a collaborative exhibition that invites audiences to engage emotionally with the stories of activists from the Alarm Phone.
Keywords: Irregular Migration, Border Imperialism, Mediterranean Sea, Fortress Europe, Alarm Phone, Border Crisis, Migrant Justice, Migrants, Refugees.